Future of Ethically Effective Leadership - Sarwar, Chaudhary Imran (2013)
This research focuses on (a) introducing and exploring ethically effective leadership, (b) introducing and testing theory on triad of typical–maximal–ideal ethically effective leadership performances, (b) theorizing and empirically testing that each of typical–maximal–ideal ethically effective leadership performance is different from each others, in other words exploring mean differences between each pair of typical–maximal–ideal effective leadership performances, (c) introducing, theorizing, and testing mechanism to quantify respondents’ intrinsic desire and inherent potential to enhance their ethically effective leadership performances, (d) exploring precedents of each of typical–maximal–ideal ethically effective leadership performances, and finally (e) exploring bases and feasibility of virtual, robotic, and mixed reality ethically effective leadership that may or may not be same as conventional ethically effective leadership. This paper explores global leadership aspect of ethically effective leadership performance at three data collection levels (via typical, maximal, and ideal effective leadership performances) adding precision to assessment of ethically effective leadership and resolving an important challenge (precise assessment) to ethical leadership development. It explores respondents’ typical ethically effective leadership performance E_T, their maximal ethically effective leadership performance E_M, and their ideal ethically effective leadership performance E_I. It presents non-western perspectives on ethically effective leadership disregarding homogenization of leadership behavior. It advances our insight into ethical leadership development by empirically identifying presence, direction and magnitude of respondents’ (a) intrinsic desire and (b) existing intrinsic potential for alteration of their ethically effective leadership. Means of typical ethically effective leadership performance E_T, maximal ethically effective leadership performance E_M, and ideal ethically effective leadership performance E_I are distinct. Typical ethically effective leadership performance E_T is positively associated with maximal ethically effective leadership performance E_M and ideal ethically effective leadership performance E_I. This article concludes that the selected leaders report their ideal ethically effective leadership performance E_I to be higher than their typical ethically effective leadership performance E_T and maximal ethically effective leadership performance E_M depicting significant intrinsic desire for 14 % enhancing their ethically effective leadership performance. Respondents have significant existing intrinsic potential for 10 % enhancing their ethically effective leadership performance. Regression constants for regression models for typical ethically effective leadership performance E_T, maximal ethically effective leadership performance E_M and ideal ethically effective leadership performance E_I are significant depicting that the researchers have to look for other variables to fully explain variance in typical ethically effective leadership performance E_T, maximal ethically effective leadership performance E_M and ideal ethically effective leadership performance E_I. Regression coefficient of typical ethically effective leadership performance E_T is significant in model for ideal ethically effective leadership performance E_I as well as maximal ethically effective leadership performance E_M and vice versa. So, the paper suggests that training strategies may be feasible to alter typical ethically effective leadership performance E_T and maximal ethically effective leadership performance E_M in such a way as to bring it closer to ideal ethically effective leadership performance E_I but for this, researchers have to look for other variables too.
Keywords: Mixed reality ethically effective leadership; Robotic ethically effective leadership; Virtual ethically effective leadership; Conventional ethically effective leadership; Inherent potential to enhance ethically effective leadership performance; Intrinsic desire to enhance ethically effective leadership performance; Ideal ethically effective leadership performance; Maximal ethically effective leadership performance; Typical ethically effective leadership performance; Ethically effective leadership